Biomedical,clinical and environmental applications of platinum-based nanohybrids: An updated review - Yerpude, Sachin T.; Potbhare, Ajay K.; Bhilkar, Pavan; Rai, Alok R.; Singh, Raghvendra P.; Abdala, Ahmed A.; Adhikari, Rameshwar; Sharma, Rohit; Chaudhary, Ratiram G. (Environmental research, 2023)
Platinum nanoparticles (Pt NPs) have numerous applications in various sectors, including pharmacology, nanomedicine, cancer therapy, radiotherapy, biotechnology and environment mitigation like removal of toxic metals from wastewater, photocatalytic degradation of toxic compounds, adsorption, and water splitting. The multifaceted applications of Pt NPs because of their ultra-fine structures, large surface area, tuned porosity, coordination-binding, and excellent physiochemical properties. The various types of nanohybrids (NHs) of Pt NPs can be fabricated by doping with different metal/metal oxide/polymer-based materials. There are several methods to synthesize platinum-based NHs, but biological processes are admirable because of green, economical, sustainable, and non-toxic. Due to the robust physicochemical and biological characteristics of platinum NPs, they are widely employed as nanocatalyst, antioxidant, antipathogenic, and anticancer agents. Indeed, Pt-based NHs are the subject of keen interest and substantial research area for biomedical and clinical applications. Hence, this review systematically studies antimicrobial, biological, and environmental applications of platinum and platinum-based NHs, predominantly for treating cancer and photo-thermal therapy. Applications of Pt NPs in nanomedicine and nano-diagnosis are also highlighted. Pt NPs-related nanotoxicity and the potential and opportunity for future nano-therapeutics based on Pt NPs are also discussed. [Display omitted] •Pt-based NHs exhibited outstanding applications due to its ultrafine-sizes, high surface area, and more biocompatibility.•Present review highlights biomedical, clinical and environmental applications of Pt-based NHs.•Moreover, work demonstrated photothermal therapy, radiotherapy, and cancer therapy using Pt NPs.•Toxicological effects of Pt-based NHs in nanomedicine and nanodiagnosis also discussed.